2015
DOI: 10.1002/app.42692
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recycled styrene butadiene rubber ground tire rubber: Combining X‐ray fluorescence, differential scanning calorimetry, and dynamical thermal analysis for quality control

Abstract: Appraisal of the main rubber characterization techniques for styrene butadiene rubber (SBR) was performed on standard SBR samples as well as recycled ground tire rubber (GTR) from an industrial tire recycling facility, containing a blend of SBR and natural rubber. The aim of the work was to provide additional information relevant to quality control in the field of rubber recycling. Benchmark characterization of industrial samples by inductively coupled plasma optical emission spectrometry, atomic absorption sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This non-destructive method allows rapid and quantitative determination of content of silicon (Si), sulfur (S), zinc (Zn), calcium (Ca), magnesium (Mg), aluminum (Al), and iron (Fe) in rubber compounds [27,28]. Miskolczi et al [29], and recently Liang et al [30], confirmed that the most intense signal from X-ray fluorescence spectrometry corresponds to zinc, and it is related to its high concentration in GTR. In the studied case the range is 1.22–2.33 wt %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This non-destructive method allows rapid and quantitative determination of content of silicon (Si), sulfur (S), zinc (Zn), calcium (Ca), magnesium (Mg), aluminum (Al), and iron (Fe) in rubber compounds [27,28]. Miskolczi et al [29], and recently Liang et al [30], confirmed that the most intense signal from X-ray fluorescence spectrometry corresponds to zinc, and it is related to its high concentration in GTR. In the studied case the range is 1.22–2.33 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements obtained by oscillating disc rheometer discussed later seem to confirm this statement. On the other hand, it should be pointed out that there is no simple correlation between sulfur content and cross-link density [30,32]. Higher sulfur content in the case of GTR samples modified with bitumen could also be explained by sulfur derivatives (such as hydrogen sulfide, carbon disulfide, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…After this period the oven door is opened with a gap of 3 cm to introduce oxygen gas for 30 minutes in order to achieve the total oxidation of the sample. The remaining ashes corresponds to the part of inorganic components of the GTR, basically SiO 2 , ZnO, and small quantities of Fe 2 O 3 and CaCO 3 [26]. To determine the ash content percentage the equation (4) Figure 1 shows particle size distribution of different GTR used in this study.…”
Section: A0 B0 C0mentioning
confidence: 99%
“…As expected, the presence of oxygen in air decreases the thermal stability of all materials. The highest decomposition temperature can be associated to the oxidation of carbon residues generated at lower temperatures, leading to the formation of carbon dioxide [25]. Liang et al [26] studied the existence of inorganic compounds like silicon, calcium, and zinc in the form of SiO 2 , ZnO, and CaCO 3 in GTR, individually.…”
Section: Mechanical Propertiesmentioning
confidence: 99%